IMPLEMENTASI STRATEGI BALAI LATIHAN KERJA (BLK) PADANG DALAM MENINGKATKAN KUALITAS TENAGA KERJA - Yana Restu Winanda; Adil Mubarak (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2020)
This study describes the implementation strategy of the Balai Latihan Kerja (BLK) Padang in improving the quality of labor. For conduct Competency Based Training (PBK) in order to improve the quality of the workforce, the strategies that have been set must be realized with good implementation. This research was conducted using the method qualitative descriptive. The selection of informants was carried out using a purposive technique sampling, test the validity of the data using triangulation techniques. Data collection conducted by interview and documentation study. Data analysis technique done by data reduction, data presentation, data verification. Results research shows that the implementation of strategy Balai Latihan Kerja (BLK) Padang in improving the quality of labor can be said to have already pretty well implemented. Implementation of this strategy when viewed from theory Amir has been carried out starting from who carried out, how managing the program, the budget needed, making procedures for ensure implementation and how to implement the strategy the. Although in its implementation there are still shortcomings and obstacles encountered.